Seroprevalence of Toxoplasma gondii in patients with chronic renal failure in Barck General Hospital - Wadi Al-Shati,Libya (Journal of Medical Sciences, 2023)
This study was conducted to investigate the seroprevalence of Toxoplasma gondii and the association between the infection and risk factors in chronic renal failure patients attending the hemodialysis unit in Barck General Hospital, Wadi Al Shati, Libya. 111 samples were collected, including 55 samples from patients, and 56 samples from healthy individuals. All samples were examined using the Enzyme Linked Fluorescent Assay (ELFA) test, to detect the presence of IgG & IgM antibodies. The results did not record any acute infection in patients and healthy individuals, while the rate of chronic infection was 32.7% and 35.7% in patient and healthy groups respectively without any significant statistical difference between the two groups. The results of the study showed that there was no statistically significant association between prevalence of the infection and age, sex, occupation and history of blood transfusion. The results showed a statistically significant association between prevalence of infection and contact with cats, and consumption of unpasteurized milk. The infection rate was higher among individuals with a low level of education compared to those with a higher level of education. The results showed increased infection rate in patients hand long exposure to hemodialysis, as the highest (50%) was in the period of 11-15 years, and the lowest  was (21.1%) in the period of